# algebra

posted by .

f(x) = 3x² + 2
x= 3
my question, do I start by solving x² first then multiply by 3 and adding 2

f(3= 3 * 9 + 2 = 29
or do I multiply first
3*3 =9² +2 = 83
I'm pretty sure we resolve the exponents first but need some help

• algebra -

sub in 3 for x

• algebra -

Use BEDMAS

B - brackets, (if any)
E - exponents
D - divisions in the order they occur
M - Multiplications in the order they occur
A - Additions in the order they occur
S - Subtraction in the order they occur

Yes, you are correct in the order you did the calculation the first time
f(3) = 3(3^2) + 2
= 3(9) + 2
= 27+2
= 29

## Similar Questions

2. ### Algebra

Please help to find x, y 1. 8x-y=17 6x+y=11 2. 5x-2y=17 2x+3y=3 Question no.1 8x-y=17 6x+y=11 (adding the equation) __________ (-y and +y will be 0) 14x =28 Taking variables to one side x=28 __ 14 14*2=28 therefore x=2 substitute this …
3. ### need guidance on an algebra problem

20 x+3(y-1)=11 2(x-y)+8y = 28 multiply out 20 x+3y-3=11 - Is this correct?
4. ### Algebra Sq Rt

to multiply the sq rt of 3 cubed by the sq rt of 9 cubed I first need to factor them?
5. ### math

35 divided by [9 plus (9-7) minus 4] plus 10 times 3..can someone please explain how to do this problem math - Evan, Tuesday, May 11, 2010 at 8:37pm think of "Please Excuse My Dear Aunt Sally" P is for paranthesis first E is for exponents …
6. ### math

35 divided by [9 plus (9-7) minus 4] plus 10 times 3..can someone please explain how to do this problem math - Evan, Tuesday, May 11, 2010 at 8:37pm think of "Please Excuse My Dear Aunt Sally" P is for paranthesis first E is for exponents …
7. ### Math

The problem to solve is: (x+20)(x-12)(x+4)>0 but I can't figure out how to do this right so I left off the >0 and tried to solve the equation. x+20 evaluates to x+20 x-12 evaluates to x-12 Multiplying x+20 by x-12 is a classic …
8. ### algebra II

Select the best possible first step to solving the system by first eliminating the y variable. x + 8y = –4 2x – 4y = –13 Multiply the first equation by 2. Multiply the second equation by 2. Multiply the first equation by –2. …
9. ### maths algebra

HI STEVE, THANKS for your reply back it was the wrong answer the one you worked, yes a hard question, here is an example of simultaneous questions. x-2/3 + y-1/4 =13/12 (1) 2-x/2 + 3+y/3 =11/6 (2) first step is to get rid of fractions. …
10. ### pre-calculus 11

-x/(x-3) + 2x/(x+2) (x-1) x (x-2) (x+2)/(x-3)(x-3) my question is should i multiply first and then do the adding or subtracting through a LCD or should i do the adding first?

More Similar Questions